-
If A = {a, d}, B = {b, c, e} and C = {b, c, f}, then A × (B - C) =
-
- (A × B) - (A × C)
- (A × B)
- A × C
- None of these
- (A × B) - (A × C)
Correct Option: A
we can calculate below as per given question,
we can calculate below as per given question,
(B − C) = { b, c, e } – { b, c, f } = { e }
A × (B − C) = { a, d } x { e }
(A × B) = { a, d } x { b, c, e }
(A × C) = { a, d } x { b, c, f }
∴ A × (B − C) = {(a, e), (d, e)} ...........…(1)
Also, (A × B) – (A × C) = {(a, e), (d, e)} ..........…(2)
Hence, from (1) and (2), we have
A × (B − C) = (A × B) – (A × C).